Retrospective study of cases of rupture uterus - Arora, Manju; Jindal, Sunita; Gupta, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study aimed to evaluate the risk factors, clinical presentation, management, maternal and perinatal outcome of patients with rupture uterus. Methods: In this study, clinical records of 14 cases of rupture uterus occurring between January 2001 to August 2004 were reviewed. Results: During this period 17312 deliveries were conducted and 14 cases of rupture uterus were managed. Incidence of rupture uterus was 0,8/1000 deliveries. In 10/14 (71.4%) of cases, rupture occurred in scarred uterus (either of cesarean delivery or of any surgery).9/14 (64.2%) women had rupture of previous cesarean section scar and 4/14 (28.5%) women had rupture of unscarred uterus .7/14 (50%) women had more than one risk factor responsible for rupture uterus. 10/14 (71.4%) women were unbooked.10/14 (71.4%) women had subtotal hysterectomy; 4/14 (28.5%) had repair of scar site. Invariably blood had to be transfused in every case per and post-operatively.6/14 (42.8%) of fetuses could be salvaged; in 7/14 (50%) women; there was intrauterine death, while another (7.14%) woman had preterm neonatal death. Conclusions: Uterine rupture is a preventable complication. In our study, most of women had no antenatal check-up and/or managed initially by untrained personnel. Antenatal and intranatal care, identification of high-risk cases and education of the people about supervised pregnancy and delivery will reduce the occurrence of uterine rupture.